THRIVE RESILIENCE PROGRAM FOR TEENS: EXAMINING SOCIAL EMOTIONAL LEARNING, SELF-ESTEEM, AND PERCEPTIONS OF HARM REGARDING SUBSTANCE ABUSE - Magen Branham; Alex Casteel; Elizabeth Moore (Journal of Scholarly Engagement)
The THRIVE Resilience Program for Teens aims to mitigate adolescent substance abuse through psychoeducation and resilience-building strategies. This study evaluated the program's effectiveness in enhancing social-emotional learning (SEL), self-esteem, and perceptions of harm regarding substance use. The study comprised three distinct investigations: (1) validated the Perceived Harm of Substance Use Scale (PHSUS), (2) assessed changes in perceptions of harm post-program completion, and (3) examined shifts in SEL and self-esteem. Findings indicated that the PHSUS is a reliable instrument, and the program significantly increases students' perceptions of substance use harm. However, while SEL improvements were significant, changes in self-esteem were not statistically significant. The study underscores the THRIVE program's potential to foster resilience and reduce substance abuse risks among adolescents, suggesting areas for further research and program enhancement. Keywords: substance abuse, resilience, social emotional learning